Unpacking User Satisfaction in OTT Platforms : The Mediating Role of User Engagement - Basha, Shaik Mahaboob; Viswanatha Reddy, C. (Indian Journal of Marketing, 2026)
Purpose : The research aimed to analyze how user engagement acted as a mediating factor in the association among various aspects of the OTT platform experience and overall user satisfaction (US). Integrating the technology acceptance model into this study provided insights into user experience with OTT platforms. Design/Methodology/Approach : This study used a quantitative approach. It was based on primary data collected from a sample of 384 OTT users via a structured survey. The study tested the impact of perceived usefulness (PU) and social influence (SI) on user satisfaction (US). The study also delineated the mediating role of user engagement and the moderating effect of technological readiness (TR) on the US. Moreover, the study tested the impact of predictor variables on the response variable using PLS-SEM. Findings : The study found that the US was vital for OTT platforms to remain competitive and deliver an extraordinary user experience. User engagement (UE) was a noteworthy positive mediator between user experience and satisfaction. A positive user experience led to superior engagement, which, in turn, amplified satisfaction. Practical Implications : This study’s findings offered valuable insights for OTT service providers, underscoring the importance of enhancing platform usability, leveraging SI, and upholding UE to optimize US. The platform managers gave greater consideration to visual elements, such as colors, design, and structure, which improved the sensorial experience. Originality/Value : This study offered unique insights into OTT platforms in the US, focusing on the mediating role of UE in relation to PU, SI, US, and technological readiness.